2022
DOI: 10.1021/jacs.2c01056
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Key Role of Distortion in Bioorthogonal Tetrazine Tools That Defy the Reactivity/Stability Trade-Off

Abstract: The tetrazine/trans-cyclooctene ligation stands out from the bioorthogonal toolbox due to its exceptional reaction kinetics, enabling multiple molecular technologies in vitro and in living systems. Highly reactive 2-pyridyl-substituted tetrazines have become state of the art for time-critical processes and selective reactions at very low concentrations. It is widely accepted that the enhanced reactivity of these chemical tools is attributed to the electron-withdrawing effect of the heteroaryl substituent. In c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 54 publications
3
69
0
Order By: Relevance
“…Steric effects are the main reasons why monosubstituted 3-phenyl-1,2,4,5-tetrazines (H-Tzs) typically have 70-fold-increased activity compared to methyl-or phenyl-substituted Tzs [43]. Recently, Svatunek and al. showed that distortion effects between the aromatic and the tetrazine rings can increase the reactivity of the molecule [44]. Increased distortion led to faster rate constants (Figure 3C) [44].…”
Section: Reactivity Of Tzsmentioning
confidence: 98%
See 4 more Smart Citations
“…Steric effects are the main reasons why monosubstituted 3-phenyl-1,2,4,5-tetrazines (H-Tzs) typically have 70-fold-increased activity compared to methyl-or phenyl-substituted Tzs [43]. Recently, Svatunek and al. showed that distortion effects between the aromatic and the tetrazine rings can increase the reactivity of the molecule [44]. Increased distortion led to faster rate constants (Figure 3C) [44].…”
Section: Reactivity Of Tzsmentioning
confidence: 98%
“…Recently, Svatunek and al. showed that distortion effects between the aromatic and the tetrazine rings can increase the reactivity of the molecule [44]. Increased distortion led to faster rate constants (Figure 3C) [44].…”
Section: Reactivity Of Tzsmentioning
confidence: 98%
See 3 more Smart Citations